Nr5a2 promotes cancer stem cell properties and tumorigenesis in nonsmall cell lung cancer by regulating Nanog - Ting Ye; Jingyuan Li; Zhiwei Sun; Yongli Liu; Liangsheng Kong; Shixia Zhou; Junlin Tang; Jianyu Wang; H. Rosie Xing (Cancer Medicine)
Abstract Lung cancer has the highest mortality rate due to late diagnosis and high incidence of metastasis. Cancer stem cells (CSCs) are a subgroup of cancer cells with self‐renewal capability similar to that of normal stem cells (NSCs). While CSCs may play an important role in cancer progression, mechanisms underlying CSC self‐renewal and the relationship between self‐renewal of the NSCs and CSCs remain elusive. The orphan nuclear receptor Nr5a2 is a transcriptional factor, and a regulator of stemness of embryonic stem cells and induced pluripotent stem cells. However, whether Nr5a2 regulates the self‐renewal of lung CSCs is unknown. Here, we showed the diagnostic and prognostic values of elevated Nr5a2 expression in human lung cancer. We generated the mouse LLC‐SD lung carcinoma CSC cellular model in which Nr5a2 expression was enhanced. Using the LLC‐SD model, through transient and stable siRNA interference of Nr5a2 expression, we provided convincing evidence for a regulatory role of Nr5a2 in the maintenance of lung CSC self‐renewal and stem cell properties in vitro. Further, using the syngeneic and orthotopic lung transplantation model, we elucidated augmented cancer biological properties associated with Nr5a2 promotion of LLC‐SD self‐renewal. More importantly, we revealed that Nr5a2’s regulatory role in promoting LLC‐SD self‐renewal is mediated by transcriptional activation of its direct target Nanog. Taken together, in this study, we have provided convincing evidence in vitro and in vivo demonstrating that Nr5a2 can induce lung CSC properties and promote tumorigenesis and progression through transcriptional up‐regulation of Nanog.